Information technologies as a factor of increase of use effectiveness of natural and cultural heritage for tourism development - Kravtsov, Sergiy (My University, 2005)
This work shows the importance of providing tourist resources information. Same examples of solving the problem of tourist product information shortage abroad are given. On the basis of these examples we suggest opening an information center in the Donbass region with the purpose of creation of more effective region potential. Special attention is given to receiving Polish tourists in connection with deepening of Poland-Ukraine relations.
Keywords: tourist information center; tourist business; destinations; туристсько-інформаційний центр; туристичний бізнес; дестинації; кафедра туристичного та готельного бізнесу